MOTIVASI DAN PERILAKU PENGGEMAR K-POP DI DAERAH ISTIMEWA YOGYAKARTA - Vania Rosalin Irmanto; Fandy Tjiptono (Modus, 2013)
Korean Pop (K-Pop) has been a huge sensation all around the world. Te current study investigated motivation and behavior of K-Pop fans in Daerah Istimewa Yog yakarta (DIY ). Specifcally, it addressed four main issues: (1) why do youths in DIY love K-Pop? (2) how did the K-Pop communities emerge in DIY? (3) what have the members done in their K-Pop communities? and (4) how strong is the emotional bond among the K-Pop community members?Te present study employed exploratory qualitative research method, i.e. phenomenological approach, using in-depth interviews as the main data collection method. Fifteen members of fveÂ  K-Pop communities (3 males and 12 females) participated in the interviews. In addition, direct observation on several K-Pop communities were conducted to gain comprehensive insights into what specifc activities the members have been doing. Secondary data sources were also consulted, such as websites (www.allkpop.com, www. koreanindo.wordpress.com, and www.asianfanatics.net), magazines (My Idol and Asian Star), and tabloids (Asian Plus).It is found that the main drivers of K-Pop sensation in Indonesia, in particular in DIY, include physical attractiveness of the actors/actresses, energic dances, similar ages with the performers, and so forth. Te big fans of K-Pop are willing to copy their idolsâ€™ appearances, listen and watch K-Pop music and clips, look for news about K-Pop, create fanfction, share information among fans, purchase Korean-made electronics, learn more about Korean culture and language, as well as watch the live concerts. Te emergence of several K-Pop communities has facilitated the communication and interaction among the fans. Several implications were drawn based on these fndings.Keywords : Korean Pop (K-Pop), phenomenological approach, brand community, K-Pop community.